PENGARUH MODEL PEMBELAJARAN DIRECT INSTRUCTIONTERHADAP HASIL BELAJAR TENTANG GERAK LURUS BERUBAH BERATURAN DI SMAN 2 PONTIANAK - Saputra, Agus; Djudin, Tomo; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe study aims to determine the effect of direct instruction model towards the student’s outcome in the linear motion in class X MIPA SMA 2 Pontianak. This research conducted true-experimental design with pretest-postest control group design. The determination of to be sampled taking use intact group, class of X MIPA I with total 27students have been selected as sample the course of this experiment and second grade of X MIPA IV with total 27students school’s tuition that we have been selected as the control group.On the basis of t-test result, tcount 1,237 >ttable 1,674 for significant level . The result show that there is no significant different of the student’s outcomes possessed by experimental group and control group. This research is expected as an alternative learning by the teacher and student’s in the difficulty in learning. Keywords : Direct Instruction, The LinearMotion, Student’s Outcome